'Our life has turned upside down! And nobody cares.'. Issue 3 (December 2016) - Lewis, Jerome
Abstract : Many hunter-gatherers today find themselves caught between the dominance of neoliberal perspectives on development and progress that focus on extractive opportunities for supplying markets with natural resources, and on conservationists' views of landscapes as wildernesses that require protection from any human activity, apart from their own. This dual occupation of hunter-gatherer land in the Congo Basin is putting huge pressure on the BaYaka Pygmies' and their neighbours' lifestyles and livelihoods. After giving their views to camera in a short film (https://ishgr.org/hunter-gatherer-voices/ ), the article examines some of the underlying assumptions about environments that legitimate the current structural and actual violence experienced by these hunter-gatherers. The article ends with a request for more accounts of the pressures facing hunter-gatherers, so we better understand them, and to assist in thinking about what we might do to support this vital part of humanity's cultural diversity.